Isolation and Cytotoxic Activity Test of Alkaloids from Dichloromethane Fraction of Bark of Tampa Badak (Voacanga foetida (Blume) Rolfe) Against T47D Cell Line - Adriani Susanty; Nurdina Putri; Ihsan Ikhtiarudin; Novia Sinata; Dira Dira; Fatma Sri Wahyuni; Dachriyanus Dachriyanus (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2023)
Cancer is a problem in the health sector because this disease has an increasing incidence of morbidity and mortality. While the treatment still leaves some drug side effects, which cause discomfort for cancers sufferers. The arises because most cancer drugs work non-selectively. Because of some of the problems above, it is necessary to encourage the search for alternative drugs treatment of cancer. Voacanga foetida (Blume) Rolfe (Apocynaceae) is a species of plant from the genus Voacanga known as the tampa badak from West Sumatra. This plant is known to be source of indole alkaloids and also bis-indole alkaloids potential as cancer drugs. Therefore, in this study we are interested to explore the potency of this plant as natural product sources with potential cytotoxic activity. The study was started from the isolation process and continued by characterization of the isolated compounds and then testing their cytotoxic activity T47D breast cancer cell line. The isolation process of alkaloid compounds were performed by acid-base extraction, liquid-liquid fractionation, and followed by separation using column chromatography. Then,the potency of cytotoxic activity of the isolates were screened through Brine Shrimp Lethality Test (BSLT) method and evaluated by MTT assay. The structure of three isolated alkaloids (VFB-DB1.1; VFB-DB2.1; and VFB-DB2.2) were charachterized using spectroscopic analyses, including UV and FT-IR. One isolated compound (VFB-DB1.1) was also characterized using 1H NMR spectroscopy. Based on the similarity of 1H NMR spectra of isolated compound when compared with the literature, compound VFB-DB1.1 was identified as voacangine. Then, the BSLT and MTT assay result showed that VFB-DB1.1 exhibited LC50 value of 15.8 µg/mL againt Artemia salina L.and IC50 value of 8.9 µg/mL against T47D breast cancer cells, respectively.